1999
DOI: 10.1086/302611
|View full text |Cite
|
Sign up to set email alerts
|

A Founder Mutation in the GK1 Gene Is Responsible for Galactokinase Deficiency in Roma (Gypsies)

Abstract: Galactokinase deficiency is an inborn error in the first step of galactose metabolism. Its major clinical manifestation is the development of cataracts in the first weeks of life. It has also been suggested that carriers of the deficiency are predisposed to presenile cataracts developing at age 20-50 years. Newborn screening data suggest that the gene frequency is very low worldwide but is higher among the Roma in Europe. Since the cloning of the galactokinase gene (GK1) in 1995, only two disease-causing mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 15 publications
3
56
0
1
Order By: Relevance
“…Genomic DNA was amplified by polymerase chain reaction (PCR) with primers 5′-CTG GAG ACC ACT CCC ATC CTT TCT-3′ (forward) and 5′-GAT GTG GCC ATC ACA TTC GTC AGA T-3′ (reverse). PCR cycling was in a touchdown regime described previously (Kalaydjieva et al 1999).…”
Section: Ace Genotypingmentioning
confidence: 99%
“…Genomic DNA was amplified by polymerase chain reaction (PCR) with primers 5′-CTG GAG ACC ACT CCC ATC CTT TCT-3′ (forward) and 5′-GAT GTG GCC ATC ACA TTC GTC AGA T-3′ (reverse). PCR cycling was in a touchdown regime described previously (Kalaydjieva et al 1999).…”
Section: Ace Genotypingmentioning
confidence: 99%
“…Interest in the genetics of the Vlax Roma has resulted in the identification of several novel single gene disorders and private founder mutations, Hereditary Motor and Sensory Neuropathy types Lom 4,5 and Russe, 6,7 Congenital Cataracts Facial Dysmorphism Neuropathy Syndrome 8,9 and galactokinase deficiency. 10,11 A population genetic study of three groups of Vlax Roma 12 revealed limited diversity, with a single ancestral Y chromosome lineage shared by 73% of males. The Vlax Roma, who account for a substantial proportion of the overall Gypsy population, thus qualify among the most restricted founder popula-tions of Europe whose potential for the study of genetically complex disorders is still to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…GALK deficiency is diagnosed in (<1/100,000) US newborns but may be more common in some populations (e.g., the Romani) (Hennermann et al 2011;Janzen et al 2011;Kalaydjieva et al 1999;Sangiuolo et al 2004). …”
Section: Classic and Duarte Galactosemiamentioning
confidence: 99%